2008
DOI: 10.1038/ejhg.2008.26
|View full text |Cite
|
Sign up to set email alerts
|

No association between MUTYH and MSH6 germline mutations in 64 HNPCC patients

Abstract: Hereditary non-polyposis colorectal cancer (HNPCC) is an autosomal dominant tumour predisposition syndrome caused by germline mutations in mismatch repair (MMR) genes. In contrast to MLH1 and MSH2, germline mutations in MSH6 are associated with a milder and particularly variable phenotype. Based on the reported interaction of the MMR complex and the base excision repair protein MUTYH, it was hypothesised that MUTYH mutations serve as phenotypical modifiers in HNPCC families. Recently, a significantly higher fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…This finding is consistent with other studies: Steinke et al [19] found that the frequency of monoallelic MUTYH mutations in MSH6 mutation carriers with colorectal cancer (2/64, 3.1 %) was not significantly higher than that of controls (9/577, 1.6 %, p = 0.30); Ashton et al [22] found that the frequency of MUTYH mutations in MLH1 and MSH2 mutation carriers (2/209, 1 %) was not higher than that of controls (4/296, 1.35 %; p = 0.69); van Puijenbroek et al [21] found no evidence of a combined effect of heterozygous MSH6 and MUTYH mutations, except perhaps for urothelial tumors; and Gorgens et al [23] found only one monoallelic MUTYH mutation of c.1187G>A p.(Gly396Asp) in 50 individuals with suspected HNPCC compared with no MUTYH mutation in 116 controls. Further, Stormorken et al [20] reported that frequency of monoallelic MUTYH mutations in individuals with HNPCC, HNPCC-like or dominantly inherited late-onset colorectal cancer (2/96, 2 %) was not more than expected by chance, and concluded that monoallelic MUTYH mutations may not increase risk of cancer in these individuals.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is consistent with other studies: Steinke et al [19] found that the frequency of monoallelic MUTYH mutations in MSH6 mutation carriers with colorectal cancer (2/64, 3.1 %) was not significantly higher than that of controls (9/577, 1.6 %, p = 0.30); Ashton et al [22] found that the frequency of MUTYH mutations in MLH1 and MSH2 mutation carriers (2/209, 1 %) was not higher than that of controls (4/296, 1.35 %; p = 0.69); van Puijenbroek et al [21] found no evidence of a combined effect of heterozygous MSH6 and MUTYH mutations, except perhaps for urothelial tumors; and Gorgens et al [23] found only one monoallelic MUTYH mutation of c.1187G>A p.(Gly396Asp) in 50 individuals with suspected HNPCC compared with no MUTYH mutation in 116 controls. Further, Stormorken et al [20] reported that frequency of monoallelic MUTYH mutations in individuals with HNPCC, HNPCC-like or dominantly inherited late-onset colorectal cancer (2/96, 2 %) was not more than expected by chance, and concluded that monoallelic MUTYH mutations may not increase risk of cancer in these individuals.…”
Section: Discussionsupporting
confidence: 94%
“…[17, 18] Other studies, however, have observed no such associations. [19-23] In this study, we aimed to estimate the risk of colorectal cancer for carriers of both a MUTYH mutation and a MMR gene mutation compared with carriers of monoallelic MUTYH mutation alone and carriers of a MMR gene mutation alone.…”
Section: Introductionmentioning
confidence: 99%
“…Niessen et al [10], found a significantly higher frequency of monoallelic MUTYH mutations in MSH6 missense mutation carriers (20%) than in Caucasian controls (1.5%, P = 0.001) and Dutch colorectal and endometrial cancer patients without MSH6 gene mutation (0.7%, P = 0.002). In contrast, Steinke et al [11] failed to find this association when they examined the MSH6 mutation carriers of the German HNPCC Consortium for MUTYH mutations.…”
Section: Discussionmentioning
confidence: 81%
“…One study has previously reported a significantly higher frequency of monoallelic MUTYH mutations in CRC patients carrying missense MSH6 mutations [10], whereas another has failed to find such correlation [11]. A third study showed that MSH6/MUTYH heterozygote mutation carriers display a predominant Lynch syndrome molecular tumor phenotype, and that abrogation of both MSH6 and MUTYH repair genes might be mutually exclusive in humans [12].…”
Section: Introductionmentioning
confidence: 96%
“…Liu et al [14] described an index subject from a LS family with two heterozygous variants (c.546-2A>G and c.1852_1853AA>GC); only the former segregated with LS in the family. Similarly, Steinke et al [15], described the co-occurrence of the p.Lys618Ala (c.1852_1853AA>GC) variant with the MSH6 p.Arg1068X (c.3202C>T) deleterious variant.…”
Section: Discussionmentioning
confidence: 99%